2019
DOI: 10.1016/j.tranon.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of CD47-SIRPα Signal in Cholangiocarcinoma Potentiates Tumor-Associated Macrophage-Mediated Phagocytosis and Suppresses Intrahepatic Metastasis

Abstract: The involvement of chronic inflammation in cholangiocarcinoma (CCA) progression is well established. Cluster of differentiation 47 (CD47) is mutually expressed in various cancers and serves as a protective signal for phagocytic elimination. CD47 signaling blockage is a recent treatment strategy; however, little is known regarding CD47 in CCA. Therefore, the potential use of CD47 targeting in CCA was focused. CD47 was highly expressed in CCA compared to hepatocellular carcinoma (HCC). Disturbance of CD47-signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 47 publications
2
42
0
Order By: Relevance
“…A similar strategy targeting macrophages is also developing by blocking CD47 from binding its receptor signal regulatory protein‐α (SIRPα) on macrophage surface 413 . It has been reported that interfering of CD47‐SIRPα interaction by blocking antibodies could promote the phagocytosis of TAMs and consequently suppresses cholangiocarcinoma growth and metastasis 414 . Nowadays, a number of CD47‐SIRPα axis blockers, such as Hu5F9‐G4, CC‐90002, SRF231, ALX148, and IBI188, are under clinical trials 413 …”
Section: Pharmacological Modulation Of Tamsmentioning
confidence: 99%
“…A similar strategy targeting macrophages is also developing by blocking CD47 from binding its receptor signal regulatory protein‐α (SIRPα) on macrophage surface 413 . It has been reported that interfering of CD47‐SIRPα interaction by blocking antibodies could promote the phagocytosis of TAMs and consequently suppresses cholangiocarcinoma growth and metastasis 414 . Nowadays, a number of CD47‐SIRPα axis blockers, such as Hu5F9‐G4, CC‐90002, SRF231, ALX148, and IBI188, are under clinical trials 413 …”
Section: Pharmacological Modulation Of Tamsmentioning
confidence: 99%
“…One to two million cells of each cell line were transplanted subcutaneously into both flanks of Balb/c RJ mice. For intrasplenic transplantation, 5 × 10 4 cells were injected intrasplenically as previously described [38]. Tissues, spleen, and liver were removed at 1 month after transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…CCA cells express higher CD47 than HCC and serve as a "don't eat me signal", thus deceiving macrophages by binding to macrophages SIRPa. The blockage of CD47-SIRPa interactions by anti-CD47 results in increased macrophage infiltration and potentiated macrophage phagocytosis, leading to decreased cancer colonization in mice models [88]. Besides, macrophages have complex regulation effects on other immune cells of the TME.…”
Section: Other Immune Escape Mechanismsmentioning
confidence: 99%